KEY ASPECTS OF THE RELIGIONS STUDIES RESEARCH METHODOLOGY - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article analyzes the main problems of research methodology in contemporary religious studies. Provided by definition a term such as "religious paradigm", " metho in religion", " methodology in religion"; revealed foundations of systematic methodology in religious studies.